Effect of MgSO4·7H2O on the hydration of Portland cement. (10th March 2023) - Zhu, Jiahui; Liu, Zanqun; Zheng, Keren; Huang, Ju; Cui, Yu
Highlights: A strong barrier of gypsum-Mg(OH)2 -hydration product attached to the clinker surface. Mg(OH)2 has a high surface energy and a strong surface electronegativity. The MPC has a milder early hydration process. Abstract: MgSO4 is usually found in the groundwater or seawater and can influence the early hydration of Portland cement. In this paper, the reaction kinetics of the early hydration of the MgSO4 ·7H2 O + Portland cement clinker (MPC) was revealed compared with the CaSO4 ·2H2 O + Portland cement clinker (OPC) by means of isothermal calorimetry, chemical shrinkage and solid–liquid phase analysis. The test results indicated that MgSO4 ·7H2 O had more pronounced retarding effect on Portland cement clinker hydration than CaSO4 ·2H2 O. The MPC system had longer initial time and final time than OPC system. In the initial period and induction period of MPC system, Mg(OH)2 and CaSO4 ·2H2 O precipitated on not only the C3 A partials but also on the C3 S partials, and prevented the flash-set of clinker. The early hydration of C3 A and C3 S were both retrained by the combined retardation of Mg(OH)2, CaSO4 ·2H2 O and hydration products, which resulted to a slower hydration rate of MPC than OPC before the deceleration period. The intense hydration of C3 A and C3 S were postponed and appeared in the deceleration period of MPC compared with OPC, which ultimately caused a deeper hydration of MPC than OPC.